2013
DOI: 10.1371/journal.pone.0064092
|View full text |Cite
|
Sign up to set email alerts
|

Role of Nitric Oxide and CCAAT/Enhancer-Binding Protein Transcription Factor in Statin-Dependent Induction of Heme Oxygenase-1 in Mouse Macrophages

Abstract: The effect of statins on heme oxygenase-1 (HO-1) was compared in 2 murine cell lines, RAW 264.7 and J774A.1 cell lines, and in primary peritoneal macrophages of BALB/c or C57BL/6 mice. The role of endogenous nitric oxide and the type of transcription factors involved were explored. Simvastatin and fluvastatin induced HO-1. Pretreatment of cells with l-NMMA or 1400 W, two different nitric oxide synthase inhibitors, partially blocked statin-dependent induction of HO-1 in RAW 264.7 and J774A.1 but not in primary … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 45 publications
0
5
0
Order By: Relevance
“…We have previously shown that statins inhibits COX-2, a proinflammatory enzyme in monocytes in a Rac and NF-κB–dependent manner [21]. In addition statins have been shown to induce HO-1 expression and to inhibit the production of IL-6 and TNF-α in macrophages stimulated with LPS [16, 18, 37].…”
Section: Discussionmentioning
confidence: 99%
“…We have previously shown that statins inhibits COX-2, a proinflammatory enzyme in monocytes in a Rac and NF-κB–dependent manner [21]. In addition statins have been shown to induce HO-1 expression and to inhibit the production of IL-6 and TNF-α in macrophages stimulated with LPS [16, 18, 37].…”
Section: Discussionmentioning
confidence: 99%
“…These authors observed that treatment of the cells with NO donor nitroprusside (3 mM) for 8 h upregulated HO-1 levels in control cells to a higher extent than in Pin1 deficient cells and argued that Nrf2/ARE-mediated transcriptional activity is negatively controlled by Pin1 in fibroblasts [137]. However, the expression of HO-1 is controlled by both Nrf2 and AP-1 via partially overlapping AREs and TPA-responsive elements in the gene promotor [138], and Mouawad et al [139] showed that NO-dependent expression of HO-1 is controlled by transcription factors C/EBPβ and AP-1 in macrophages [139]. Therefore, we suggest the possibility that NO-activated AP-1 could induce HO-1 gene expression more efficiently in the absence of Pin1-mediated Nrf2 nuclear translocation.…”
Section: Discussionmentioning
confidence: 99%
“…Based on the findings of these studies, S100A12 expression was transcriptionally up-regulated by CCAAT/enhancer-binding protein and activator protein. Since statins reportedly promote expression of other genes by activating these transcription factors 33,34) , further studies are needed to explore underlying mechanisms for atorvastatinmediated reduction of serum S100A12 levels.…”
Section: Discussionmentioning
confidence: 99%